2013
DOI: 10.1108/00220411311295351
|View full text |Cite
|
Sign up to set email alerts
|

Connecting with new information landscapes: information literacy practices of refugees

Abstract: Purpose: The purpose of the research reported in this article is to understand how refugees learn to engage with a complex, multimodal information landscape and how their information literacy practice may be constructed to enable them to connect and be included in their new information landscape. Methodology: The study is framed through practice and socio-cultural theories. A qualitative research design is employed including semi-structured face-to-face interviews and focus groups which are thematically analys… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
235
0
5

Year Published

2015
2015
2019
2019

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 201 publications
(257 citation statements)
references
References 29 publications
5
235
0
5
Order By: Relevance
“…In a study of refugees trying to access e-government services, Lloyd et al [12] found that the information poverty they experience was a product of the social exclusion of the participants as a result of barriers e-services can erect. Such information poverty can lead to "limited support networks, [an] inability to access the labour market, alienation from society and poorer educational outcomes" [15].…”
Section: Related Workmentioning
confidence: 99%
See 1 more Smart Citation
“…In a study of refugees trying to access e-government services, Lloyd et al [12] found that the information poverty they experience was a product of the social exclusion of the participants as a result of barriers e-services can erect. Such information poverty can lead to "limited support networks, [an] inability to access the labour market, alienation from society and poorer educational outcomes" [15].…”
Section: Related Workmentioning
confidence: 99%
“…However, in instances where these social groups may not be attainable or their knowledge and experience is also deficient can have dire repercussions for those members of society who already face significant barriers [12]. In an effort to address these concerns the UK government are currently running both standard services (face-to-face, postal and over the telephone) and digital services simultaneously but it is not inconceivable that standard services will (eventually) be phased out.…”
Section: Introductionmentioning
confidence: 99%
“…Lloyd et al [16] found that refugees trying to access e-government services experience information poverty due to social exclusion of the participants as a result of barriers e-services can erect. Vinson suggests that such information poverty can lead to serious negative outcomes, including "limited support networks, [an] inability to access the labour market, alienation from society and poorer educational outcomes" [23].…”
Section: Related Workmentioning
confidence: 99%
“…This issue is made more serious by the policies of most national governments, the UK's included, to begin transitioning their services from a "traditional" face-toface and paper-based paradigm to "e-services," where provision is made through purely digital means [11]. For those in society, however, who are not adept in the use of such technologies, or are not able to readily make sense of the important information delivered through them, this raises concerns around the barriers that may be erected and the risk this poses of segregating users, especially those in vulnerable groups [13], such as refugees and migrants [16].…”
Section: Introductionmentioning
confidence: 99%
“…The study is informed by existing research that suggests that there is a relationship between language learning and information literacy [1][2] as well as research that looks at the information literacy practices of immigrants and more widely at their information behaviour which suggest that social exclusion can be seen as an information problem [3], transferring information practices is a significant issue [4], and that there is an association between immigrants and information poverty [5]. ESOL learners are adults living in the UK who are learning English as part of adult basic skills provision.…”
Section: Introductionmentioning
confidence: 99%